2006
DOI: 10.1002/mds.20999
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of Parkinson's disease in a developing country: A retrospective cost analysis in Shanghai, China

Abstract: We investigated economic costs from patients with Parkinson's disease (PD) in Shanghai, China, which could be used as a baseline for future evaluations. Data were collected from 190 patients by interview during 1-year period. Direct medical care costs averaged approximately Chinese yuan, renminbi (RMB) 4,305 (USD 519, or EUR 410) per year per patient, of which drugs (RMB 2,677) accounted for the major costly component. Nonmedical direct costs were much less than direct health care costs, averaging approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 19 publications
3
37
2
Order By: Relevance
“…Cubo et al [31] reported direct costs of EUR 10,524 per PD patient per year, which was similar to our findings. The annual direct costs of PD in our study were comparable to those reported from other Western European countries (EUR 7,920 in Sweden [5] , EUR 8,160 in Germany [10] , EUR 9,500 in the UK [32] ) but higher than those from countries in Eastern Europe (EUR 6,700 in the Czech Republic [11] , EUR 3,520 in Russia [12] ) or Asia (EUR 630 in India [33] , EUR 820 in China [34] ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Cubo et al [31] reported direct costs of EUR 10,524 per PD patient per year, which was similar to our findings. The annual direct costs of PD in our study were comparable to those reported from other Western European countries (EUR 7,920 in Sweden [5] , EUR 8,160 in Germany [10] , EUR 9,500 in the UK [32] ) but higher than those from countries in Eastern Europe (EUR 6,700 in the Czech Republic [11] , EUR 3,520 in Russia [12] ) or Asia (EUR 630 in India [33] , EUR 820 in China [34] ).…”
Section: Discussionsupporting
confidence: 80%
“…In our Italian cohort of patients with PD, dyskinesias were independent determinants of total costs. Interestingly, depression was identified as a cost-driving factor in our study though the majority of previous studies did not include depression in their multivariate analysis [8,10,32,34] . Future largescale studies should clarify if depression is a country-specific, cost-driving, independent factor in the Italian PD patient population.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, levodopa equivalent dose and number of drugs taken were closely associated with drug therapy cost. These results indicate that the economic burden of Chinese patients with PD is heavy [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified a reduced quality of life and, thus, a potential socioeconomic impact of the diseases. To date, studies on the economic impact of PD and AP have involved the use of questionnaires with selected patients, the economic burden being estimated from this information [27][28][29][30][31][32]. The identification or assumptions of costs in these studies have primarily addressed direct costs, whereas indirect costs have not been identified.…”
Section: Introductionmentioning
confidence: 99%